2000
DOI: 10.1017/s0960258500000118
|View full text |Cite
|
Sign up to set email alerts
|

Large-seeded spices are less dependent on light for germination than small-seeded ones

Abstract: Germination in light and darkness was compared after cold stratification of seeds of 54 species known or suspected to accumulate persistent seed banks. Germination became less dependent on light with increasing seed mass. This pattern was clear in a direct correlation of individual species data (P<0.0001) as well as when considering phylogenetically independent contrasts (P<0.001). The latter analysis suggests that light response and seed mass coevolved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
358
4
22

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(422 citation statements)
references
References 32 publications
38
358
4
22
Order By: Relevance
“…Mean weight per seed of a species was calculated using all available seed samples of this species. Values from the literature (Salisbury 1942;Lhotska and Chrtkova 1978;Grime et al 1981;Mü ller-Schneider 1983;Bakker et al 1997;Cerletti 1997;Akinola et al 1998;Milberg et al 2000;VanAssche et al 2002) complemented our measurements of 14 species (see Table 1). The age of the seed samples from the collection of the Botanical Institute (Basel, Switzerland) had no significant influence on seed weight (regression analysis with 47 seed samples from 11 randomly chosen species).…”
Section: Methodssupporting
confidence: 76%
“…Mean weight per seed of a species was calculated using all available seed samples of this species. Values from the literature (Salisbury 1942;Lhotska and Chrtkova 1978;Grime et al 1981;Mü ller-Schneider 1983;Bakker et al 1997;Cerletti 1997;Akinola et al 1998;Milberg et al 2000;VanAssche et al 2002) complemented our measurements of 14 species (see Table 1). The age of the seed samples from the collection of the Botanical Institute (Basel, Switzerland) had no significant influence on seed weight (regression analysis with 47 seed samples from 11 randomly chosen species).…”
Section: Methodssupporting
confidence: 76%
“…Since light can only penetrate a few millimeters from the top of the soil surface, seeds found below this depth do not germinate; and even in dark-requiring species, those seedlings would die before reaching the soil surface, especially if they are small owing to the smaller seedling size (see below). Data on other ecosystems suggest that seeds that are smaller are more likely to require light for germination than larger seeds (Milberg et al, 2000;Jankowska-Blaszczuk and Daws, 2007). In a recent study, Wu et al (2013 ) found a similar pattern in alpine species of Qinghai-Tibetan Plateau.…”
Section: Light Requirementmentioning
confidence: 85%
“…Light is an important environmental factor stimulating germination in many seeds (Milberg et al, 2000). The requirement of light for germination has been one of the potential determinants driving species to accumulate a persistent seed bank (Baskin and Baskin, 1998;Milberg et al, 2000;Pons and Fenner, 2000).…”
Section: Light Requirementmentioning
confidence: 99%
See 1 more Smart Citation
“…Light is a critical regulator of germination in small seeds (Milberg et al 2000, Pearson et al 2003, Seo et al 2009). Light sensitivity of seeds is dependent on the action of phytochromes and change their sensitivity as a function of temperature (Heschel et al 2007, Franklin 2009.…”
Section: Introductionmentioning
confidence: 99%